Polymorphisms in the TNFa but not in TNFb microsatellite and correlation with trypanosomiasis in mice - Iraqi, F.A.; Teale, A.J. (1998)
The tumor necrosis factor (TNF) locus comprises the tandemly arranged genes coding for Tnfa (cachectin)and Tnfb (lymphotoxin-alpha) (Semon et al. 1987). In mice, the TNF locus is located on chromosome 17 (MMU17) in the major histocompatibility complex (MHC)region. Tnfa and soluble lymphotoxin alpha are cytokines with similar biological activities.